Avaliação da viabilidade técnico-econômica da etapa reacional da hidrogenação seletiva de CO2 a metanol - Valadares, Arthur Coutinho (Universidade Federal de São Carlos, 2021)
Methanol is a very important raw material used in the chemical industry, being applied in the production of other chemicals, such as formaldehyde, acetic acid and plastics. In the last decade, the annual methanol production doubled, reaching 98 million metric tons (Mton), and is estimated to be 500 Mton in 2050. However, due to being produced from fossil sources, like coal and natural gas, there is a big release of carbon dioxide. Nowadays, about 10% (0,3 Gton) of all CO2 produced by the chemical industry comes from the methanol cycle, which encompasses from production to consumption. If new sources of methanol, renewables, are not delevoped, it is estimated that in 2050, 1,5Gton of CO2 will be released annually in the cycle of this alcohol. The major obstacle to produce methanol with less impact on the environment, currently, is the cost to produce hydrogen gas. There are different lines of studies that seek the feasibility of producing methanol from new sources, including: the generation of synthesis gas from biomass (Bio-methanol or Green methanol); hydrogen production from electrolysis, with the use of renewable energies (E-methanol or green methanol); and carbon capture (blue methanol), which is the case studied in this work. The objective of this work was to simulate, using the software Aspen Plus® and a kinetics developed on a laboratory scale available in the literature, and verify the economic feasibility of the reaction step on an industrial scale. The simulations were divided into three stages: the initial stage was a simulation of the thermodynamics of the system, to verify the response of the simulation with values presented in scientific publications; then, the kinetics reported in the literature were implemented, and a validation of the simulated results was carried out based on the empirical data; finally, it carried out an analysis study varying the operating conditions (reactor temperature and pressure, feed flow, catalyst mass) to assess the economic viability of the process, using the Net Present Value (NPV) as a metric. It is expected as a result of this work to find the conditions that can make the process viable or even indicate possible paths to economic viability. With the function obtained, it was possible to optimize the NPV within the limits of the kinetics under study, however, no case was found in which such value is positive, therefore, with limitations imposed by the kinetics used, profit with sales and cost of inputs, it is not feasible to perform the implementation of such a project
Techno-economic evaluation of reactional step of selective hydrogenation of CO2 to methanol
Keywords: Metanol; Simulação; Hidrogenação; CO2; Methanol; Simulation; Hydrogenation; ENGENHARIAS::ENGENHARIA QUIMICA